Pharmacological Inhibition of WIP1 Sensitizes Acute Myeloid Leukemia Cells to the MDM2 Inhibitor Nutlin-3a - Fontana, Maria Chiara (Biomedicines, 2021)
In acute myeloid leukemia (AML), the restoration of p53 activity through MDM2 inhibition proved efficacy in combinatorial therapies. WIP1, encoded from PPM1D, is a negative regulator of p53. We evaluated PPM1D expression and explored the therapeutic efficacy of WIP1 inhibitor (WIP1i) GSK2830371, in association with the MDM2 inhibitor Nutlin-3a (Nut-3a) in AML cell lines and primary samples. PPM1D transcript levels were higher in young patients compared with older ones and in core-binding-factor AML compared with other cytogenetic subgroups. In contrast, its expression was reduced in NPM1-mutated (mut, irrespective of FLT3-ITD status) or TP53-mut cases compared with wild-type (wt) ones. Either Nut-3a, and moderately WIP1i, as single agent decreased cell viability of TP53-wt cells (MV-4-11, MOLM-13, OCI-AML3) in a time/dosage-dependent manner, but not of TP53-mut cells (HEL, KASUMI-1, NOMO-1). The drug combination synergistically reduced viability and induced apoptosis in TP53-wt AML cell line and primary cells, but not in TP53-mut cells. Gene expression and immunoblotting analyses showed increased p53, MDM2 and p21 levels in treated TP53-wt cells and highlighted the enrichment of MYC, PI3K-AKT-mTOR and inflammation-related signatures upon WIP1i, Nut-3a and their combination, respectively, in the MV-4-11 TP53-wt model. This study demonstrated that WIP1 is a promising therapeutic target to enhance Nut-3a efficacy in TP53-wt AML.